Some problems of legal regulation of the institution of guardianship and tutelage in Ukraine - Дробчак, Алла; Кравець, Анастасія (Актуальні проблеми правознавства, 2018)
For today, the importance of guardianship and tutelage bodies can’t be overemphasized. At a time when the country is in an undeclared war, many families have suffered from the effects of hostilities, many children have been left without parental care and need protection. Against the backdrop of a decline in the social security of citizens and economic problems, the drop in the standard of living, the increase in the crime situation, the large number of internally displaced citizens, and the protection of children is of particular importance.